Performance and emission evaluation of diesel engine fuelled with biodiesel produced from high free fatty acid crude soyabean oil. Issue 4 (3rd July 2016) - Hira, Aman; Das, D.
ABSTRACT: This paper is based on the experimental investigations of the performance and emissions of a CI engine. The biodiesel produced from soybean crude oil was prepared by method of alkaline catalyzed transesterification of soybean oil being blended with mineral diesel. Experiments were carried out using pure diesel (B0) and different blending ratios of B10, B20, B30, B40 and B50. The performance and emission characteristics of different blends were compared with the result from a standard diesel engine. The performance characteristics show that an increase in brake thermal efficiency (BTE) and a decrease in brake specific fuel consumption (BSFC) were observed using blend B20 at the maximum load as compared to mineral diesel. A BTE of 37.07% and 36.43% and a BSFC of 0.24 kg/kWh and 0.23 kg/kWh was observed with blend B20 and diesel respectively. In addition, it was observed that a significant reduction of CO, HC and smoke occurred with an increase of load as compared to pure diesel. However CO2 and NOx emissions were slightly increased for all blends, which indicated complete combustion of fuel in the combustion chamber.